2001
DOI: 10.1007/s007750100232
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cisplatin with methionine- and histidine-containing peptides: competition between backbone binding, macrochelation and peptide cleavage

Abstract: The pH- and time-dependent reaction of cis-[PtCl2(NH3)2] with the methionine- and histidine-containing peptides H-Gly-Met-OH, H-Gly-Gly-Met-OH, Ac-His-Gly-Met-OH, and Ac-His-(Ala)3-Met-OH at 313 K has been investigated by ion-pairing reverse phase HPLC and NMR spectroscopy. For equimolar solutions (c=0.8 mM, pH approximately equals 3 or 8.8), initial formation of the kinetically favored S-bound complex is followed by relatively rapid metallation of the neighboring methionine amide nitrogen NM to afford a kappa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 12 publications
4
64
1
Order By: Relevance
“…The complex reacted rather slowly (days), as the reaction kinetics expended additionally on the rate of replacement of chloride ligands with water molecules that reacted with the peptide substrate according to the Lewis acid mechanisms. The sequence specificity observed for cisplatin was analogous to that described above for other Pt(II) and Pd(II) complexes [61,62].…”
Section: Anchoring At Met Cys and His Side Chains: Pd(ii) And Pt(ii)supporting
confidence: 74%
“…The complex reacted rather slowly (days), as the reaction kinetics expended additionally on the rate of replacement of chloride ligands with water molecules that reacted with the peptide substrate according to the Lewis acid mechanisms. The sequence specificity observed for cisplatin was analogous to that described above for other Pt(II) and Pd(II) complexes [61,62].…”
Section: Anchoring At Met Cys and His Side Chains: Pd(ii) And Pt(ii)supporting
confidence: 74%
“…Our MudPIT analyses have now demonstrated that Y150 (or Y148) and D375 (or E376) are characteristic binding sites for cisplatin in HSA, and that these, and possibly other O-donor sites, can exhibit a remarkable degree of kinetic stability. Because coordination by these residues is more rapid than for S-donor residues, [32][33][34] it is reasonable to assume that they play an important role in the initial transA C H T U N G T R E N N U N G port of the metallodrug. The relative thermodynamic weakness of PtÀO bonds means, however, that kO-coordinated cisplatin should be capable of slowly migrating to softer binding sites (e.g., DNA nucleobases) on reaching a target tumour cell.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Previous studies of cisplatin binding to HSA [13][14][15][16] and other proteins [29][30][31] have emphasised the important role of the softer cysteine and methionine sulfur atoms as preferred targets, and our present investigation does, of course, confirm C34 and establish M329 and M548 as specific binding residues in HSA, and M256 in Trfe. O-donor atoms, however, are known to be kinetically preferred [32][33][34] as initial binding sites for cisplatin, and inspection of the 1 H, 15 N HSQC NMR spectrum taken for a cisplatin-HSA mixture (310 K, pH 6.4) after 2 h in the presence of added chloride (Figure 2 a in ref. [15]) confirms the presence of a number of intense cross peaks that are attributable to PtÀO binding trans to an ammine ligand (NH 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This explains the reactivity of cisplatin with many thiol-containing proteins. Although cisplatin has been shown to form complexes with histidine, aspartic acid, glutamic acid, and glycine, it is unlikely that these complexes will form in plasma or within cells in preference to complexes with protein thiol groups (1,16,24,31). The much higher reactivity of cisplatin with thiol groups is well established.…”
Section: Discussionmentioning
confidence: 99%